Estudo de técnicas de problemas inversos bidimensionais: aplicação em processos de usinagem - Lima, Frederico Romagnoli Silveira (1996)
This work treats techniques for solving inverse heat conduction problems related to tools used in machining. The surface heat flux can be estimated from experimental and calculated temperature data. An evaluation of boundary conditions of metal cutting indicates the complexity of the thermal problem and a three-dimensional analysis is necessary. I-Iowever, in a first study, the use of a simplified hypothesis enables one-dimensional and two-dimensional analyses initially. The heat source due the machining process was simulated numerically to permit a great flexibility in the analysis of the technique used. This work presents the results of both the one-dimensional and two-dimensional analyses. In the one-dimensional analysis, the tool rake face appears to a one-dimensional linear heat transfer history. In the two-dimensional analysis, the linear heat transfer history varies with time and position. In that case, the heat appeared to be lost laterally. The evaluation of results indicates the cases that the methods can be applied successfully.